THE DIET PROBLEM REVISITED. - Bassi, L.J. (American Economist)
Updates the original problem to account for the much more rapid rise in food prices than the consumer price index and the increased number of basic nutritional requirements and food varieties. Solution of the linear programming problem using the simplex algorithm; Minimization of an objective function representing the cost of food purchases subject to constraints reflecting the 16 nutritional requirement.